Avaliação da função motora e fadiga de pacientes com Atrofia Muscular Espinhal tipo 2 e 3 - Ana Carolina Monteiro Lessa de Moura (2022)
Spinal Muscular Atrophy (SMA) is considered a neuromuscular disease, which leads to progressive muscle weakness, fatigue and consequently affects functional motor skills. Objectives: To assess motor function in patients with SMA type 2 and 3, using the Hammersmith Functional Motor Scale Expanded (HFMSE) motor scale, based on its translation and cross-cultural adaptation, and to use appropriate instruments to assess fatigue in this group of patients. Methodology: The process of translating and transcultural adaptation of the HFMSE into Portuguese was carried out. The scale validation process was performed in 28 patients followed up by the Neuromuscular Diseases Outpatient Clinic of the Hospital das Clínicas; Validation consisted of applying the HFMSE scale and analyzing its correlation with other relevant variables, such as fatigue, muscle strength and respiratory function. Fatigue was assessed through physiological tests (nine hole peg test and shuttle walk test) and perception (Fatigue severity scale and PedsQL MFS) and was described and correlated with other variables in the present study. Results: The inter-examiner reliability analysis shows that the ICC was equal to 1.00 and the Kappa agreement analysis for each of the HFMSE items was > 0.80, showing a very satisfactory reliability index. In the validation of the HFMSE, a high correlation was observed with measures of muscle strength and vital capacity (VC %) (p < 0.05). There is a statistically significant difference (p < 0.05) between patients with and without contracture in relation to the scores obtained in the HFMSE, where patients with contracture have significantly lower scores than patients with no contracture. There are statistically significant correlations between the mean time of the nine hole peg test and the HFMSE and muscle strength of elbow flexors (p < 0.001). Due to the sample size, it was not possible to establish a statistically significant correlation between the other fatigue variables. Conclusion: Through the study, it was possible to conclude that the HFMSE - version translated into Portuguese, proved to be effective as an instrument for assessing the motor function of patients with SMA type 2 and 3. Unfortunately, the motor assessments that are currently used in trials and clinical practice, do not specifically measure fatigue. Thus, an additional tool is needed to assess fatigue in this group of patients.